Effect of high velocity oxy-fuel (HVOF) coatings on fatigue behaviour of carbon steel - Moh Halmi, Mohamad Ariff (2021)
Nowadays, the application of high velocity oxy-fuel (HVOF) spraying is widely used in various industries. This is due to its ability to improve the wear, erosion and corrosion resistance of components. However, by taking consideration of mechanical properties and fatigue behaviour into cognisance, the consequence of the HVOF thermal spraying coating on the components remain debatable. In this research, the main objectives are to obtain the mechanical properties, investigate the fatigue behaviour and observe the microstructure of the uncoated and coated carbon steel. The morphology, chemical composition and the phase of the specimen were characterized using an optical microscope (OM), scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and x-ray diffraction (XRD). The microhardness of the specimen was tested with loads of 0.05 HV within dwell time of 10 s. Tensile test was carried out with a strain rate of 0.5 mm/min and a dog bone shaped specimen in accordance with ASTM-E8 standard. Fatigue test was performed under the stress ratio, R = -1 in accordance with ASTM-E466 by tension-compression cyclic loading (sine wave) with a frequency of 20 Hz. The results showed that the microhardness of the coated steel decreased by 40% and the yield strength of the coated steel decreased by 9.5% due to the increment of the substrate´s grain size resulting from the high HVOF flame temperature (2750 ˚C). The increment of coating thickness from 0.15 to 0.35 mm decreased the yield strength of the coated by 4.4% as due to the long-time exposure to high HVOF flame temperature. From the grit-blasting treatment, the embedment of the grit particles, cracks and notches on the substrate´s surface are the main reasons for the reduction of the tensile strength of the substrate by 9.1%. Similar behaviours are shown by the fatigue properties, as the HVOF coated steel showed a fatigue strength’s reduction of 17% due to the increment of the substrate’s grain size. These findings conclude that HVOF spraying process gives negative impact on the mechanical properties and fatigue properties.